The development a prototype of student result analyzer system for CS220 students portal using PHP / Mohd Hussin Abd. Salam - Abd. Salam, Mohd Hussin (2005)
This project is designed to develop A Prototype of Student Result Analyzer System for CS220 Students portal for Bachelor of Science (Hons.) Information Technology. This system is designed for the Faculty of Information Technology and Quantitative Sciences. The target users of this system are students and lecturers. At the beginning of every semester students will receive their examination result for previous semester, there's a student who a failed and pass on the subject they taken. This situation will remain the same on every semester. We don't know the performance of those students, who the top and who are the bottom on each part. And of course as a one stop center for the lecturers upload any notes and material so the students can download it. Fortunately, this web portal system will fill that emptiness. This smart system will solve most of your problems and you can do it all by yourself.